Interaction between Escherichia coli DNA polymerase IV and single-stranded DNA-binding protein is required for DNA synthesis on SSB-coated DNA - Furukohri, Asako (Oxford University Press, 2012)
DNA polymerase IV (Pol IV) is one of three translesion polymerases in Escherichia coli. A mass spectrometry study revealed that single-stranded DNA-binding protein (SSB) in lysates prepared from exponentially-growing cells has a strong affinity for column-immobilized Pol IV. We found that purified SSB binds directly to Pol IV in a pull-down assay, whereas SSBΔC8, a mutant protein lacking the C-terminal tail, failed to interact with Pol IV. These results show that the interaction between Pol IV and SSB is mediated by the C-terminal tail of SSB. When polymerase activity was tested on an SSBΔC8-coated template, we observed a strong inhibition of Pol IV activity. Competition experiments using a synthetic peptide containing the amino acid sequence of SSB tail revealed that the chain-elongating capacity of Pol IV was greatly impaired when the interaction between Pol IV and SSB tail was inhibited. These results demonstrate that Pol IV requires the interaction with the C-terminal tail of SSB to replicate DNA efficiently when the template ssDNA is covered with SSB. We speculate that at the primer/template junction, Pol IV interacts with the tail of the nearest SSB tetramer on the template, and that this interaction allows the polymerase to travel along the template while disassembling SSB.